High production of 2, 3-butanediol from biodiesel-derived crude glycerol by metabolically engineered Klebsiella oxytoca M1. Issue 1 (December 2015) - Cho, Sukhyeong; Kim, Taeyeon; Woo, Han; Kim, Yunje; Lee, Jinwon; Um, Youngsoon
Abstract Background 2, 3-Butanediol (2, 3-BDO) is a promising bio-based chemical because of its wide industrial applications. Previous studies on microbial production of 2, 3-BDO has focused on sugar fermentation. Alternatively, biodiesel-derived crude glycerol can be used as a cheap resource for 2, 3-BDO production; however, a considerable formation of 1, 3-propanediol (1, 3-PDO) and low concentration, productivity, and yield of 2, 3-BDO from glycerol fermentation are limitations. Results Here, we report a high production of 2, 3-BDO from crude glycerol using the engineeredKlebsiella oxytoca M3 in whichpduC (encoding glycerol dehydratase large subunit) andldhA (encoding lactate dehydrogenase) were deleted to reduce the formation of 1, 3-PDO and lactic acid. In fed-batch fermentation with the parent strainK. oxytoca M1, crude glycerol was more effective than pure glycerol as a carbon source in 2, 3-BDO production (59.4 vs. 73.8 g/L) and by-product reduction (1, 3-PDO, 8.9 vs. 3.7 g/L; lactic acid, 18.6 vs. 9.8 g/L). When the double mutant was used in fed-batch fermentation with pure glycerol, cell growth and glycerol consumption were significantly enhanced and 2, 3-BDO production was 1.9-fold higher than that of the parent strain (59.4 vs. 115.0 g/L) with 6.9 g/L of 1, 3-PDO and a small amount of lactic acid (0.7 g/L). Notably, when crude glycerol was supplied, the double mutant showed 1, 3-PDO-free 2, 3-BDO production with high concentration (131.5 g/L), productivity (0.84 g/L/h), and yield (0.44 g/g crude glycerol). This result is the highest 2, 3-BDO production from glycerol fermentation to date. Conclusions 2, 3-BDO production from glycerol was dramatically enhanced by disruption of thepduC andldhA genes inK. oxytoca M1 and 1, 3-PDO-free 2, 3-BDO production was achieved by using the double mutant and crude glycerol. 2, 3-BDO production obtained in this study is comparable to 2, 3-BDO production from sugar fermentation, demonstrating the feasibility of economic industrial 2, 3-BDO production using crude glycerol.